Amnesia in an actor: Learning and re-learning of play passages despite severe autobiographical amnesia. (June 2015) - Kopelman, Michael D.; Morton, John
Abstract: We describe the case of an accomplished actor, whom we term AB, who suffered severe amnesia following a cardiac arrest and hypoxic brain damage, affecting medial temporal and thalamic structures. His performance on standard episodic memory tests, and on measures of retrograde amnesia, including autobiographical memory, was severely impaired. When presented with passages from plays he had not appeared in, AB showed a severe impairment at the first learning trial, but thereafter showed a 'normal' learning curve for this semantically and syntactically complex material. On being presented with passages from plays he had performed in the past, AB did not show any recognition of them whatsoever, as one might expect from his severe episodic memory impairment. However, AB showed a striking benefit (savings score) in relearning passages he had previously performed, compared with new passages, despite not having any autobiographical recall of having performed the relearned passages before. Moreover, although his initial recall performance in learning these passages was impaired compared with healthy control actors of similar age and experience, AB demonstrated the same incremental learning rate on subsequent learning trials of the passages as did the controls. We conclude that, although severely impaired at the first learning trial (on both 'new' and 'old' passages), AB was able to employ his long-established semantic and procedural skills to attempt the task, and that thereafter he showed a 'normal' rate of incremental learning from a lower baseline.